Belarus in the historical policy of Poland (2005–2020) - Tsimbal, Alexander Georgievich (Journal of the Belarusian State University. History, 2020)
The political use of history to affirm dominant political discourses and form a system of loyalty has become an integral part of modern domestic and foreign policy. Poland represents a classic example of the instrumentalisation of history. History has become the subject of controversy, and sometimes acute conflicts of Poland with Russia, Ukraine, Germany and Lithuania. Until recently, Belarus remained a blank spot in Polish historical policy. The aim of the research is to study the Belarusian direction of Polish historical policy. The research is based on an institutional approach. The article reveals the influence of the foreign factor on the formation of Polish historical policy. The conceptual foundations and goals of the Polish historical policy in relation to Belarus are analysed. The characteristics of actors, institutions and practices of Polish historical policy are given. In conclusion, we raise the question of assessing the effectiveness of Polish historical policy in Belarus.
Keywords: politics of memory; Poland; Belarus; Institute of National Remembrance; historical policy